The Analysis of Vocational Teacher Readiness at Culinary Education Program in Participating in Online Professional Teacher Education Program - Saramoya, Siva; Basyirun, Basyirun; Murdani, Murdani (Universitas Negeri Semarang, 2018)
This study aims to: (1) describe the readiness of vocational school teacher of culinary program in the implementation of online - based Professional Teacher Education (PTE); (2) find factors driving and inhibiting the readiness of teachers in the implementation of online – based PTE. This quantitative descriptive study was conducted at SMK N 6 Semarang (Tourism Vocational School) and SMK N 1 Bawen (Agricultural Vocational School) involving 14 productive skill teachers of the Culinary Program. The data were obtained using questionnaires and analyzed descriptively using percentages. The results of the study were: 57% of teachers had very high readiness, 36% were high and only 7% had sufficient readiness. The factors supporting the readiness of productive teacher skill at culinary program during the implementation of online – based PTE are facilities and infrastructure (79%), Knowledge on the field of culinary program (86%), pedagogical competence (79%), personal competence (86%), social competence (86%) and professional competence (93%). Factors inhibiting the readiness of the online – based PPG is the computer literacy (57%) and networking access (64%). It was concluded that teachers have a high readiness in the implementation of online – based PTE. Factors supporting the readiness of the online PTE are infrastructure, the knowledge, pedagogical competence, personal competence, social and professional competence. The inhibiting factor is the ability to operate a computer and access the network.